Bounded Solutions for Some Classes of Difference Equations with Operator Coefficients - Gorodnii, M. F.; Lagoda, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain necessary and sufficient conditions for the existence and uniqueness of bounded solutions for some classes of linear one- and two-parameter difference equations with operator coefficients in a Banach space.